Party fragmentation, political predispositions, and delayed voting decisions - Pignataro López, Adrián (2024)
Research has found that as the effective number of political parties increases, people are more likely to delay their voting decisions. Yet, since voters have different political predispositions, theory suggests that the effects of fragmentation are not equal for all, but stronger for non-partisans and low interest voters. The analysis of survey data from 24 countries shows that party fragmentation does increase the probability of a late voting decision of all partisan and non-partisan voters at all levels of political interest. A more detailed measure of time of voting decision, however, evidences that partisans and voters with high political interest are less influenced by the number of parties. All in all, these findings highlight an understudied consequence of party fragmentation: it impacts the time of voting decision for most voters in democracies.